Biochar and its importance in adsorption of antibiotic and heavy metals from aqueous solutions - M. Aly, Hesham (Ecological Questions, 2017)
This short communication relates to carbon-rich material referred to as biochar. In the subsequent sections, the text presents old and modern methods of production, physiochemical characteristics and miscellaneous applications of biochar in environmental protection, e.g. treatment of contaminated soil and water, as well as in agriculture for soil fertilization. The final part of the text deals with further possible, more extensive use of biochar in these two economic sectors, particularly to create carbon sink for CO2 sequestration in land cultivation, and to remove heavy metals and pharmaceutical compounds from soil and water in environmental protection.